Salmanov, Oktay - (:unkn) unknown (My University, 2026)
Oktay Salmanov Shirin graduated from the Faculty of Mechanical Engineering of the Azerbaijan Polytechnic Institute in 1986. From 1986 to 1991, he worked in Turkmenistan as a Mechanical Engineer and later as Chief Mechanical Engineer. Between 2000 and 2005, he studied at Baku State University. In 2006, he was admitted as a doctoral researcher (dissertant) at the Institute of Mathematics and Mechanics of the Azerbaijan National Academy of Sciences. In 2011, he was awarded the degree of Doctor of Philosophy (PhD) in Mathematics in the specialty 2002.01 – Mechanics of Deformable Solid Bodies. In 2025, he received the academic title of Associate Professor from the Higher Attestation Commission under the President of the Republic of Azerbaijan. Since 2013, he has been a faculty member of the Department of Higher Mathematics at the Azerbaijan University of Architecture and Construction, where he has served as Lecturer, Senior Lecturer, and Associate Professor. Dr. Salmanov is the author of 30 scientific publications, one methodological manual, and three textbooks.